IMPLEMENTASI MODEL PEMBELAJARAN DISCOVERY UNTUK MENGETAHUI KETERAMPILAN DASAR BEKERJA ILMIAH MAHASISWA IAIN PALU - Mirnawati Mirnawati (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
This study aims to determine the differences in knowledge of basic scientific work skills in students in the classroom. This research uses the Quasi Experiment method with The Non Equivalent, Pretest-Postest Design research design. The research sample consisted of 30 PGMI IAIN Palu students. The sampling technique used is Simple Random Sampling. Data collection techniques are using observation sheets. Data analysis techniques using the Normality test, Homogeneity test, and t test using the IBM SPSS Statistics 22 and Microsoft Excel programs. The results showed the significance value of Sig (2-Tailed) was 0.00 <0.05 which means that H0 was rejected and H1 was accepted. Obtained from data on differences in knowledge of basic scientific work skills for students who use the conventional learning model and for students who use the Discovery Learning learning model. It can be concluded that there is a significant difference in knowledge between students who use conventional learning models and students who use Discovery Learning learning models in the Science Concept Basic courses.